نظم ِخاندان اور معاشرتی استحکام : قرآنی تعلیمات کے تناظر میں ایک مطالعہ (Al-Qamar, 2025)
Qur'an is a complete code of life, offering guidance for personal and collective sides of human life. The family system teachings given in the Qur'an are very much part of bringing social stability. Through promoting the values of justice, kindness, respectfulness towards one another, and spirituality as a model of leadership, the family provides a source of harmony, security, and morality. This not only brings people up but also forms the basis for a balanced and strong society. A stable family builds a unified society, whereas fragile families make a contribution towards social issues and disintegration. Islam makes the nikah a firm covenant of mercy and love. The Qur'an mentions spouses as clothes for one another, representing intimacy, protection, and support for each other. Mutual respect, kindness, and compassion are emphasized as the foundations of marital relations, fostering harmony and tranquility within the family. The Qur'an establishes clear yet balanced rights and responsibilities for all family members. The husband is tasked with provision and protection, while the wife is entrusted with nurturing and household management. Both are expected to act with justice, mercy, and mutual respect. The coordination of responsibility and right is the key to household harmony. Qur'anic teachings emphasize justice and equality, providing for well-defined, complementary roles for men and women that are conducive to stability. The Qur'an offers pragmatic advice for the settlement of disagreements between spouses. Should disputes reach a boiling point, the appointment of impartial and wise arbiters from each family is recommended to settle and reconcile. The Qur'an promotes good and constructive dialogue, essential for peacemaking and intra-family cohesion. The Qur'an decidedly attaches importance to being kind and respectful to parents, reinforcing family cohesion and value transmission from one generation to another. Showing respect to parents is described as a way of developing love, respect, and cooperation in the family, ensuring social security for the elderly. This research seeks to investigate the Qur'anic teachings regarding the family structure and its central place in attaining social stability.
Keywords: Quranic Teachings; Family System; Marriage; Social Stability; Society; Family Harmony; Marital Conflict; Marriage Covenan; Mutual Respect; Marital Relations